Lúpus eritematoso sistêmico como fator de risco para aterosclerose carotídea e hipertrofia ventricular esquerda - Océa, Regina Adalva de Lucena Couto (2010)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease of high morbidity and mortality associated mainly with the activity of disease, infections and cardiovascular disease. In this condition, both premature atherosclerosis (AT) as well as left ventricular hypertrophy (LVH) are related to traditional risk factors for cardiovascular disease (CVD) and probably the peculiar characteristics of the pathophysiology of inflammatory disease. Some evidence shows the association of AT and LVH, which is considered a strong predictor for the presence of atherosclerotic plaques in carotid arteries. This study aimed to determine the frequency of AT and LVH in patients with SLE and to evaluate its relationship with traditional risk factors and factors specific to the disease. We conducted a prospective study of 70 SLE patients attending the outpatient clinic of Rheumatology, Federal University of Sergipe (UFS) and Private Practice of Rheumatology. We evaluated clinical, laboratory and research intima-media thickness of carotid arteries (CIMT) in atherosclerotic plaques and the index of left ventricular mass (LVMI), through questionnaires, the completion of the carotid duplex scan and echocardiogram, respectively. Statistical analysis was determined by multiple logistic regression, after performing descriptive statistics and odds ratios adjusted and simple. We observed the presence of AT in 34.3% of cases, LVH in 45.7% and concomitant LVH with AT in 23% of cases. AT was significantly associated with age > 50 years, systolic blood pressure (SBP), dyslipidemia, non-white race, renal disease, absence of antimalarial, late age of diagnosis, time course of disease and LVH, (p<0.05). In multivariate analysis, the relationship was demonstrated age > 50 years (OR:7.3), p = 0.01, absence of antimalarial (OR:4.7), p=0.006 and SBP (OR:1.5), p=0.05. LVH was associated with age > 50 years, not white race, hypertension (HBP), c-reactive protein > 1 mg/dL (CRP), time course of disease and AT (p <0.05). In the multivariate analysis, we found that hypertension (OR:11.4), p=0.001, CRP > 1 mg/dL (OR:8.2), p=0.004, AT (OR:6.04); p=0.02, remained linked to LVH and body mass index (BMI) > 25 kg/m² (OR:4.61), p=0.04, was added as a strong predictor of LVH. The data suggest that in SLE, the presence of AT and LVH are associated not only to some traditional risk factors for CVD such as hypertension and obesity, but also to the chronicity of the disease, its treatment; and serological markers of inflammation.